Two-photon direct laser writing of beam expansion tapers on single-mode optical fibers. (15th April 2019) - Vanmol, Koen; Tuccio, Salvatore; Panapakkam, Vivek; Thienpont, Hugo; Watté, Jan; Van Erps, Jürgen
Highlights: Flexible design and fabrication strategy for beam expansion tapers. Measurements of the refractive index of IP-DIP at telecom wavelengths. Solutions to print high aspect-ratio structures on optical fiber tips. 3D printed tapers give a relaxation in lateral misalignment tolerance. Scaling up the technique towards multi-fiber components. Abstract: Small misalignments between two standard telecom single-mode fibers in a physical contact connection can lead to large optical losses. It is known that by expanding the mode field diameter of the fiber, the misalignment tolerances can be relaxed. One of the approaches to obtain this beam expansion is to use tapers. We propose an air-clad taper structure to transmit the fundamental mode of a single-mode fiber adiabatically to a 3 times larger mode field area in physical contact expanded beam connectors. This results in a 241.4  μ m long linear taper. The taper itself is fabricated on top of a cleaved fiber facet by means of the two-photon polymerization direct laser writing technique. Experimental results for lateral misalignment show excellent agreement with simulated values and give an increase in lateral misalignment tolerance of 1  μ m (−1 dB) and 1.8  μ m (−3 dB). Total insertion losses down to 0.76 dB are measured, showing the trade-off between achievable insertion loss and misalignment tolerance relaxation. Finally, we show that the use of additive manufacturing techniques in fiber beam expansion applications make it possible to fabricate taper structures with full 3D design freedom and to upscale the process to multi-fiber components.